2004
DOI: 10.1088/0964-1726/13/4/011
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of delamination on the damped dynamic response of composite beams with piezoelectric actuators and sensors

Abstract: Experimental and analytical studies are presented investigating the effect of delamination cracks on the low-frequency dynamic response of composite beam specimens with surface attached piezoelectric actuators and sensors. Frequency response functions of laminated beams with piezoceramic actuators and piezoelectric sensors having single delamination cracks of various sizes are measured. Comparisons with mechanical actuation-accelerometer sensor configurations illustrate the sufficiency and advantages of piezoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…The accuracy of the developed mechanics is first validated for the case of pristine beams with previous models. Predicted modal frequencies of delaminated beams are also compared with previously contacted experimental results (Chrysochoidis and Saravanos, 2004). All applications were focused on composite Gr/Epoxy T300/934 beams with quasi-isotropic laminations [0/90/45/À45] s , 0.127 mm nominal ply thickness, 280 mm long and 25 mm wide.…”
Section: Materials Geometry and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of the developed mechanics is first validated for the case of pristine beams with previous models. Predicted modal frequencies of delaminated beams are also compared with previously contacted experimental results (Chrysochoidis and Saravanos, 2004). All applications were focused on composite Gr/Epoxy T300/934 beams with quasi-isotropic laminations [0/90/45/À45] s , 0.127 mm nominal ply thickness, 280 mm long and 25 mm wide.…”
Section: Materials Geometry and Assumptionsmentioning
confidence: 99%
“…Di Sciuva and Librescu (2000) presented a geometrically non-linear theory of multilayered composite plates and shells with damaged interfaces, Luo and Hanagud (2000) presented a model for describing the static, modal and dynamic response of delaminated beams using a nonlinear approach based on piecewise linear spring models between the delaminated sublaminates; Thornburgh and Chattopadhyay (2001) used a higher-order theory to model matrix cracking and delamination in laminated composite structures; Hu et al (2002) analyzed the vibration response of delaminated composite beams using a higher-order finite element with a C 0 type finite element materials; and Diaz Valdes and Soutis (1999) presented experimental work on the detection of delaminations in composite beams using piezoelectric actuator and sensor. Chrysochoidis and Saravanos (2004) investigated mainly experimentally effects of delamination on the modal parameters and frequency response functions of artificially delaminated composite beams obtained via attached piezoceramic actuators and sensors pairs and demonstrated the potential of the latter compared to other traditional sensors. Chattopadhyay et al (1999) studied the dynamics of delaminated composite plates with piezoelectric actuators using a third-order shear theory and more recently (Chattopadhyay et al, 2004) reported a refined layerwise theory for the prediction of the vibration of delaminated plates considering the crack faces interface contact using a system of nonlinear springs.…”
Section: Introductionmentioning
confidence: 99%
“…Also it can be observed in Table I that 1 C is increased which means the stiffness of the composite is decreased. Many literatures [17]- [19] propose that these phenomena occur because of delamination in case of multilayer composites. Furthermore, Zou et al in [20] states that delamination increases the damping of the structure.…”
Section: C1 Scenario 1 -Delaminationmentioning
confidence: 99%
“…Furthermore, Zou et al in [20] states that delamination increases the damping of the structure. Also Chrysochoidis et al [19] presents that the damping in the delaminated specimen changes because of variations in effective damping and stiffness properties in the delaminated sub-laminates, and friction and impacts between the crack faces. But both literatures agree that the behavior of damping is more sophisticated and is a challenging subject of research.…”
Section: C1 Scenario 1 -Delaminationmentioning
confidence: 99%
“…Such damage when left unattended can grow at alarming rate due to the singularity of the stress and strain in the vicinity of the damage. This can lead to an increase in vibration level, reduction in load carrying capacity, deterioration in the normal performance of the component, and even catastrophic failure [1][2][3]. Delamination in composites has been a topic of concern and this has been extensively reviewed [4].…”
Section: Introductionmentioning
confidence: 99%